An awareness on Islamic financing among small firms in Malaysia Industrial Estate Limited (MIEL) Lundang Industrial Area Kota Bharu - Alias, Siti Nor Najihah; Musa, Muhammad Fadhli; Aminuddin, Azwan Shah (Journal of Islamic, Social, Economics and Development, 2025)
Islamic finance presents a viable and ethical alternative for small businesses; however, its adoption among SMEs in Malaysia remains limited. This study explores the levels of awareness, sources of education, and the relationship between Islamic finance literacy and adoption among small firms in the MIEL Lundang Industrial Area. A qualitative approach was adopted, involving semi-structured interviews with six firm operators. Findings show that while general awareness of Islamic finance exists, detailed understanding—particularly regarding mechanisms and implications—is often lacking. Most respondents relied on informal sources such as social media, while formal education through seminars and workshops significantly improved comprehension and willingness to adopt. Firms with higher financial literacy were more inclined to use Islamic financing, driven by religious principles and ethical considerations. Nevertheless, perceived cost barriers and limited availability of Islamic finance experts continue to impede adoption. The study recommends targeted educational initiatives and institutional support to enhance Islamic finance literacy and promote wider SME adoption.